Pelatihan Geogebra Augmented Reality Interaktif dan Praktis kepada siswa SMAN 10 Sijunjung - Meria Ultra Gusteti; Widya Rahmalina; Suci Wulandari; Khairul Azmi; Asrina Mulyati; Rahmatul Hayati; Ria Finolia; Serly Septia Elza (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2025)
This community service activity was motivated by the challenges of integrating technology into mathematics learning, as well as the lack of teacher competence and student motivation in this regard. The methods used included identifying target schools, developing training materials, conducting interactive GeoGebra training, and evaluation and monitoring. The results showed that GeoGebra AR training effectively improved students' understanding and teachers' competence. Therefore, it can be concluded that this program succeeded in improving the quality of mathematics learning at SMAN 10 Sijunjung. Suggestions for the future are to conduct further research on the effectiveness of the program and expand the reach of training for teachers in other regions.